2022
DOI: 10.1021/acsinfecdis.2c00364
|View full text |Cite
|
Sign up to set email alerts
|

Toolkit of Approaches To Support Target-Focused Drug Discovery for Plasmodium falciparum Lysyl tRNA Synthetase

Abstract: There is a pressing need for new medicines to prevent and treat malaria. Most antimalarial drug discovery is reliant upon phenotypic screening. However, with the development of improved target validation strategies, target-focused approaches are now being utilized. Here, we describe the development of a toolkit to support the therapeutic exploitation of a promising target, lysyl tRNA synthetase ( Pf KRS). The toolkit includes resistant mutants to probe resistance mechanisms and on-target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 44 publications
3
20
0
Order By: Relevance
“… 3 , 4 The drug bead synthesis protocol specifically details the attachment of DDD02355221 ( Figure 1 ) onto an activated Sepharose resin. 1 Probe DDD02355221 is an analog of DDD01510706 , a known inhibitor of P. falciparum lysyl tRNA synthetase (KRS). 5 However, we have successfully used this procedure to prepare drug beads based upon other molecules of interest.…”
Section: Before You Beginmentioning
confidence: 99%
See 2 more Smart Citations
“… 3 , 4 The drug bead synthesis protocol specifically details the attachment of DDD02355221 ( Figure 1 ) onto an activated Sepharose resin. 1 Probe DDD02355221 is an analog of DDD01510706 , a known inhibitor of P. falciparum lysyl tRNA synthetase (KRS). 5 However, we have successfully used this procedure to prepare drug beads based upon other molecules of interest.…”
Section: Before You Beginmentioning
confidence: 99%
“…For example, DDD02355221-drug beads were prepared with 82% and 11% loading levels for the high- and low-loading drug beads respectively. 1 …”
Section: Expected Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, using multiple target identification methods in parallel can also provide confidence in targets that are consistently identified. Successful target identification programs have often combined multiple approaches, with complimentary techniques confirming both target engagement and the phenotypic relevance of identified targets ( Milne et al, 2022 ). For example, the plasmepsin inhibitors WM4, WM5 and WM382 utilised IVIEWGA to originally identify plasmepsin X as a potential target, and demonstrated that WM382 specifically bound to both plasmepsin IX and X through targeted chemoproteomic and CETSA assays ( Favuzza et al, 2020 ).…”
Section: Prospects and Challengesmentioning
confidence: 99%
“…Chemical biology tools are often developed using chemical probes as starting points 12 and adding additional functionality such as a biotin handle, click handle, or fluorescent dye. The importance of the criteria outlined above for the generation of robust, well-characterized probes therefore directly influences the performance and utility of the resulting tools.…”
mentioning
confidence: 99%